Green Synthesis Of Silver Nanoparticles From Water-Soluble Polysaccharides Of Clinacanthus Nutans Leaf: Extraction, Characterisation, Optimisation And Antibacterial Studies - Devasvaran, Kogilavanee (2023)
C. nutans has gained much attention by researchers due to its pharmacotherapeutic properties. However, the extraction method of C. nutans leaf crude polysaccharide (CNP), CNP synthesising silver nanoparticles (AgNP) and the subsequent antibacterial properties as a DNA synthesis inhibitor, has not been studied. Hence, this research aims to employ a green synthetic method to produce AgNP and assess its potential application as an antibacterial agent. Five extraction methods of CNP were employed, namely hot water (HW_CNP), ultrasound-assisted (UL_CNP), freeze-thaw (FT_CNP), alkaline (ALK_CNP) and acid (ACD_CNP). All five CNP were optimised and characterised, and their compositions were analysed. Three CNP were then selected to synthesise ACD_AgNP, ALK_AgNP, and UL_AgNP, respectively, where ALK_AgNP and UL_AgNP were optimally selected based on their synthesis conditions and their toxicity in brine shrimp was quantified. The antibacterial and potential DNA synthesis inhibition mechanism of action (MOA) of ALK_AgNP was further quantified. The results of CNP showed that ACD_CNP and FT_CNP obtained the highest and lowest extraction yield at 14.85 ± 0.25% and 4.16 ± 0.13%, respectively.